Determination of the mass attenuation coefficient for Aluminum element using (Cu,Mo) X-rays tubes - Ahmad Mohamed Kheder; Muhsin Hasan Ali (Tikrit Journal of Pure Science)
In this study the value of linear  and mass  attenuation coefficients of Aluminum element (Al) were determinated by using x-ray Cu-tube of energies CuKα (8.048) KeV, CuKβ (8.906) KeV, and Mo-tube of energies MoKα (17.480) KeV and MoKβ (19.609) KeV.the voltage between the two electrodes are up to 35 KV.The measured  values are compared with other experimental data showing a general agreement within a precision of 0.2% - 0.8%.